Empowering Women Communities through Skill Development and Leadership Programs - Mokoena, Oratilwe Penwell (Edujavare Publishing, 2025)
Women’s empowerment remains a central challenge in community development, particularly in rural settings where limited access to education, economic resources, and leadership opportunities constrains women’s potential. This community engagement program aimed to strengthen women’s capacity through integrated skill development and leadership training based on the Participatory Rural Appraisal (PRA) approach. The program involved 35 women in Desa Sukamakmur over six months, engaging them in participatory mapping, focus group discussions, workshops, and peer mentoring sessions. Data were collected through observation, interviews, and pre-post assessments, then analyzed using mixed methods, including descriptive statistics, thematic analysis, and correlation tests. The findings showed a significant increase in participants’ entrepreneurship skills and leadership confidence, supported by a strong correlation between skill acquisition and leadership capacity (r = 0.71, p < 0.01). Qualitatively, women demonstrated greater confidence, collaboration, and participation in community decision-making. The program concluded that combining practical skills with leadership empowerment fosters sustainable, community-led transformation. Its contribution lies in providing a replicable model of participatory women’s empowerment that bridges economic independence and social leadership.